Sufi Oral Narrative In Wolof At The Crossroads Of Literature, Linguistics, And Language Pedagogy - Seck MAMARAME (Akofena)
Abstract: Narratives has always been essential to human experience. From ancient myths and legends to the present day, our world has never been free of narrative. Even if some believe that there are no longer any great narratives, they cannot deny that every time one or more actions are performed in time and space, a narrative is born. Literature, linguistics and language pedagogy, or didactics, are often regarded as separate disciplines. The aim of this work is to prove that narrative, whether oral or written, can be a link between these three disciplines. We intend to prove this using a modular approach to text analysis that can be used by literature specialists, linguists and language teachers, depending on their areas of interest. This approach will be applied to Sufi oral narratives in Wolof, which we see as a common ground between literary studies, linguistics and language teaching Keywords: narrative, literature, linguistics, language pedagogy, Wolof